(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article scientifically substantiates the contribution of the outstanding representative of Kazakh children’s literature Sultan Kaliuly to children’s literature. The writer’s works are systematized and grouped by content and types. His contribution to genres such as poems, songs, poems, riddles, tongue twisters, legends and fairy tales was conditioned by the analysis of specific works. As a result of the analysis, it is proved that the writer educates the younger generation of patriots of his country who distinguish well between good and bad. Having started his career as a school teacher, the writer left many works in the genres of poetry, satire, and prose for Kazakh children. The work of the editor-in-chief of the children’s magazine “Baldyrgan”, the newspaper “Ulan” closely connected the writer with children. In his works written for preschoolers, schoolchildren, he managed to instill in children “physical education, mental education, beauty education and moral education”, as M. Zhumabayuly said. With his riddles composed from simple to complex, he expanded the knowledge, thinking of the child, encouraged him to search, think and be resourceful. S. Kaliuly’s poems have been translated into the Russian, Ukrainian, Uzbek, Georgian, Turkmen, Karakalpak, Azerbaijani languages, and he has made a great contribution to the artistic translation of the works of many writers. With his translation, Kazakh children got acquainted with the world classics.